Role of Staging Laparoscopy in Gallbladder Cancer - Sharma, A.; Thapa, P. (Kathmandu University Medical Journal, 2020)
Background Preoperative accurate staging of gallbladder cancer is still difficult. A number of patients with gallbladder cancer who undergo laparotomy for curative resection are ultimately found to have unresectable disease. The benefit of staging laparoscopy is its ability to find out the radilogical occult intraperitoneal metastasis and to spare from non-theraputic laparotomy. The role of staging laparoscopy has been extensively studied in hepatobiliary and pancreatic malignancies and found to be useful. But in recent time its utility in biliary cancers is sceptical probably because of the advent of positron emission tomography. However in gallbladder cancer it is still recommended. Objective To identify the utility of staging laparoscopy in gall bladder cancers. Method Hospital based study conducted at Nepalgunj Medical College, Nepal from October 2014 to June 2020. The patients with resectable gallbladder cancers on computed tomography were included. All patients underwent single stage staging laparoscopy. Staging laparoscopy was considered positive if the surface lesions (liver and/or peritoneal deposits) were detected. The surgery was terminated if positive. Patients with negative staging laparoscopy were proceeded with laparotomy. Result Staging laparoscopy was done in 47. The yield of staging laparoscopy was 14 (29.78%) and its accuracy was 58.33% (14/24). Out of 33 (70.21%) with negative staging laparoscopy, 10 (30.3%) had unresectable disease in laparotomy. The yield was higher in locally advanced in comparison to early disease (78.57% Vs 21.42%). Conclusion We recommend routine staging laparoscopy in gallbladder cancer, particularly when the disease is locally advanced.